2020
DOI: 10.3389/fimmu.2020.00915
|View full text |Cite
|
Sign up to set email alerts
|

GDF15 Plasma Level Is Inversely Associated With Level of Physical Activity and Correlates With Markers of Inflammation and Muscle Weakness

Abstract: Growth differentiation factor 15 (GDF15) is a stress molecule produced in response to mitochondrial, metabolic and inflammatory stress with a number of beneficial effects on metabolism. However, at the level of skeletal muscle it is still unclear whether GDF15 is beneficial or detrimental. The aim of the study was to analyse the levels of circulating GDF15 in people of different age, characterized by different level of physical activity and to seek for correlation with hematological parameters related to infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 44 publications
(66 reference statements)
10
68
2
Order By: Relevance
“…In these reports, the increase in GDF15 was around 1.5-to 2-fold, which is much less than the more than fourfold increase found here after marathon race-associated strenuous exercise. Only a study in spartathlon runner found a rise in GDF15 levels in the fourfold range found here for marathon runners (Tchou et al, 2009) whereas around threefold increase in GDF51 levels were reported after a long distance cycling race (Conte et al, 2020). During the editorial processing of the current article, a study in Marathon runners in Poland has been reported (Kaleta-Duss et al, 2020) showing a rise in GDF15 levels immediately after the race and normalization thereafter, confirming our findings.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In these reports, the increase in GDF15 was around 1.5-to 2-fold, which is much less than the more than fourfold increase found here after marathon race-associated strenuous exercise. Only a study in spartathlon runner found a rise in GDF15 levels in the fourfold range found here for marathon runners (Tchou et al, 2009) whereas around threefold increase in GDF51 levels were reported after a long distance cycling race (Conte et al, 2020). During the editorial processing of the current article, a study in Marathon runners in Poland has been reported (Kaleta-Duss et al, 2020) showing a rise in GDF15 levels immediately after the race and normalization thereafter, confirming our findings.…”
Section: Discussionsupporting
confidence: 87%
“…Numerous studies have reported that FGF21 levels increase in response to experimental acute exercise (Cuevas-Ramos et al, 2012;Kim et al, 2013;Hansen et al, 2015Hansen et al, , 2016Slusher et al, 2015;Tanimura et al, 2016;Morville et al, 2018;Sargeant et al, 2018). GDF15 has also been reported to exhibit transient elevations following an experimental single bout of exercise (Kleinert et al, 2018), a cycling race (Conte et al, 2020) and relatively time-limited sports activities such as a soccer match (Sanchis-Gomar et al, 2013) or a training session of rugby players (Galliera et al, 2014). Increased levels of GDF15 in athletes immediately after a 247-km race (the so-called Spartathlon) has also been reported (Tchou et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The cachexia-induced muscle loss protection suggests a role for GDF15 in muscle mass maintenance. Moreover, GDF15 muscle and serum levels inversely correlate with muscle cross-sectional area in chronic obstructive pulmonary disease (COPD) patients [ 126 ] and with muscle force in lower limb mobility impairments [ 127 ]. Moreover, the overexpression of GDF15 in muscle is sufficient to induce muscle atrophy [ 126 ], likely by FoxO1 and SMAD3 activation [ 128 ].…”
Section: The Role Of the Myomitokines Fgf21 And Gdf15 In Healthy Amentioning
confidence: 99%
“…Consistently, basal circulating GDF15 levels were higher in physically inactive patients with impaired mobility causing chronic walking or exercising inabilities. Contrarily, basal circulating GDF15 levels were lower in active cyclists when compared to age-matched control counterparts [ 55 ]. Taken together, these findings imply a link between the systemic response to mitochondrial stress and the muscle-mediated metabolic fitness.…”
Section: Discussionmentioning
confidence: 99%